Dengue Outbreak in Children During 2019: Experience at A Tertiary Care teaching Hospital - Datta, Mitra; Ferdousi, Asma; Haque, Salina; Jahan, Rifat; Das, Aparup; Haq, Tanjina (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Dengue outbreaks are hitting different geographic locations, different clinical manifestations are being reported recently. This study was aimed to describe the clinico-epidemiological profile and outcome of dengue infected children during 2019 dengue outbreak in Chattogram. Materials and methods: This hospital based prospective observational study was carried out in the Department of Pediatrics in Chattogram Medical College Hospital. Serologically positive dengue cases (Aged £12 years) admitted from July 2019 to December 2019 were enrolled in the study. Hospital outcome of the patient’s was recorded in terms of mortality, Length of Hospital Stay (LOS) need for ICU. Results: Out of total 192 patients as per the National Guideline 66.7% cases were classified as dengue fever without warning signs, 21.9% as dengue fever with warning signs and 11.5% as severe dengue. Overall the mean age was 7.04 (±3.23) years with male preponderance (59%). Along with fever main complaints were abdominal pain (91.7%), vomiting (47.9%) and headache (23.6%). Marked thrombocytopenia (Below 50,000) was present in 37.9%, leucopenia in 27.9% and raised haematocrit in 10.9% of cases. Average LOS was 5.2 (±1.9) days, 18 (9.5%) patients need ICU admission and there was no fatality in this series. Some clinical (Vomiting, flusihing, shock, reduced urinary output) and laboratory (Marked thrombocytopenia, leucopenia, hemoconcentration, pleural effusion and hepatomegaly) variables were associated with severity. Conclusion: Fever with abdominal pain were common presentations of dengue fever. Severe dengue patients presented with vomiting, flashing and shock. Marked thrombocytopenia and pleural effusion and/or ascites were related to shock. Appropriate and timely management is very effective in reducing case fatality. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 46-50